Multimodal political networks - Knoke, David 1947-; Diani, Mario 1957-; Hollway, James 1982-; Christopulos, Dēmētrēs 1969- (Cambridge University Press, 2021)
Research on social networks has become a significant area of investigation in the social sciences, and social network concepts and tools are widely employed across many subfields within the field. This volume introduces political theorists and researchers to new theoretical, methodological, and substantive tools for extending political network research into new realms and revitalizing established domains. The authors synthesize new understandings of multimodal political networks, consisting of two or more types of social entities - voters, politicians, parties, events, organizations, nations - and the complex relations between them. They discuss ways to theorize about multimodal connections, methods for measuring and analyzing multimodal datasets, and how the results can reveal new insights into political structures and action. Several empirical applications demonstrate in great detail how multimodal analysts can detect and visualize political communities consisting of diverse social entities
Title from publisher's bibliographic system (viewed on 17 May 2021)
Keywords: Political sociology; Soziales Netzwerk; Politisches Netzwerk